DETERMINANTS OF ENERGY USE ON PER CAPITA INCOME IN ASEAN-5 COUNTRIES - Davika, Hira; Atmanti, Hastarini Dwi (Universitas Tidar, 2025)
Economic growth continues to be enhanced with the aim of improving the welfare of its society. In implementing economic growth, it requires components that are not only human resources but also natural resources. Economic growth is positively correlated with energy use, and this can raise per capita income. This study aims to investigate how energy consumption, CO2 emissions, and foreign direct investment (FDI) affect economic growth in 5 ASEAN nations. This study uses 5 ASEAN countries that have the highest economic growth and high Carbon Emissions. This research uses the Ordinary Least Square method. (OLS). Energy use has a negative and negligible impact on GDP per capita, according to the findings of the research. GDP per capita is significantly and favorably impacted by foreign direct investment, or FDI. The impact of CO2 emissions on GDP per capita is negligible and negative. The conclusion of this research is that the variables of Carbon Emissions and Energy Consumption do not have a significant effect on GDP per capita, whereas the variable of Foreign Direct Investment (FDI) has a significant effect on GDP per capita. It is hoped that this research can serve as a basis for evaluation for future studies using more advanced methods, and of course, be useful for policymakers.